The Impact of Cognitive impairment on Clinical Symptoms, Physical Activity and Care Interactions among Residents in Assisted Living Settings. (February 2022) - Resnick, Barbara; Boltz, Marie; Galik, Elizabeth; Zhu, Shijun
The purpose of this study was to describe differences in pain, behavioral symptoms, quality of staff-resident interactions, participation in function focused care and physical activity among residents with and without cognitive impairment in assisted living. This was a secondary data analysis using baseline data from an ongoing trial testing Function Focused Care for Assisted Living using the Evidence Integration Triangle (FFC-AL-EIT). A total of 550 residents were recruited from 59 communities. The average age of participants was 89.30 ( SD = 7.63), the majority were white (98%), female (69%), had evidence of cognitive impairment (75%), and 5.16 ( SD = 1.86) comorbidities. Those with cognitive impairment had more pain, were more sedentary and less likely to engage in function focused care activities. Addressing pain and implementing interventions for those with cognitive impairment to participate in function focused care may help optimize function and physical activity in assisted living residents.